Proceedings of the 23rd ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2017
DOI: 10.1145/3097983.3098068
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Motifs

Abstract: Motifs are a powerful tool for analyzing physiological waveform data. Standard motif methods, however, ignore important contextual information (e.g., what the patient was doing at the time the data were collected). We hypothesize that these additional contextual data could increase the utility of motifs. us, we propose an extension to motifs, contextual motifs, that incorporates context. Recognizing that, o entimes, context may be unobserved or unavailable, we focus on methods to jointly infer motifs and conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…In Fox et al (2017), Fox et al propose contextual motifs as an extension to network motifs that considers the context under which a particular motif occurs to better predict hypo-and hyperglycemic events in waveform patient data. Their findings suggested that the discovery of such contextual motifs are clinically more meaningful than the contextless counterparts and lead to a more fine-grained interpretation of their meaning.…”
Section: Emotion-exchange Motifsmentioning
confidence: 99%
“…In Fox et al (2017), Fox et al propose contextual motifs as an extension to network motifs that considers the context under which a particular motif occurs to better predict hypo-and hyperglycemic events in waveform patient data. Their findings suggested that the discovery of such contextual motifs are clinically more meaningful than the contextless counterparts and lead to a more fine-grained interpretation of their meaning.…”
Section: Emotion-exchange Motifsmentioning
confidence: 99%